2007
DOI: 10.1104/pp.107.098897
|View full text |Cite
|
Sign up to set email alerts
|

Barley MLO Modulates Actin-Dependent and Actin-Independent Antifungal Defense Pathways at the Cell Periphery

Abstract: Cell polarization is a crucial process during plant development, as well as in plant-microbe interactions, and is frequently associated with extensive cytoskeletal rearrangements. In interactions of plants with inappropriate fungal pathogens (so-called non-host interactions), the actin cytoskeleton is thought to contribute to the establishment of effective barriers at the cell periphery against fungal ingress. Here, we impeded actin cytoskeleton function in various types of disease resistance using pharmacolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
159
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(168 citation statements)
references
References 90 publications
6
159
2
1
Order By: Relevance
“…Cyan fluorescent protein or yellow fluorescent protein was inserted at the C terminus of ADF in this study. As overexpression of ADF could interfere with plant development (Dong et al, 2001) and response to the powdery mildew fungus (Miklis et al, 2007), we cloned the ADF4 genomic region containing the 1.5-kb ADF4 promoter, introns, and 39 UTR for examination of the subcellular localization and function of ADF in the Arabidopsis-G. orontii interaction. The ADF4 genomic construct fused with GFP inserted upstream of the first exon (GFP-ADF4) was transformed into adf4, and T2 plants were examined.…”
Section: Nuclear Localization and Phosphorylation Of Adf4 Are Both Immentioning
confidence: 99%
See 1 more Smart Citation
“…Cyan fluorescent protein or yellow fluorescent protein was inserted at the C terminus of ADF in this study. As overexpression of ADF could interfere with plant development (Dong et al, 2001) and response to the powdery mildew fungus (Miklis et al, 2007), we cloned the ADF4 genomic region containing the 1.5-kb ADF4 promoter, introns, and 39 UTR for examination of the subcellular localization and function of ADF in the Arabidopsis-G. orontii interaction. The ADF4 genomic construct fused with GFP inserted upstream of the first exon (GFP-ADF4) was transformed into adf4, and T2 plants were examined.…”
Section: Nuclear Localization and Phosphorylation Of Adf4 Are Both Immentioning
confidence: 99%
“…Transient overexpression of HvADF3, AtADF1, AtADF5, AtADF6, AtADF7, and AtADF11 (called AtADF12 in this article), but not the overexpression of AtADF2, AtADF3, AtADF4, and AtADF9, partially breaks down the resistance of barley (Hordeum vulgare) mlo against the barley-adapted powdery mildew fungus Blumeria graminis f. sp. hordei (Bgh; Miklis et al, 2007). The localization of RPW8.2 to the membrane surrounding the powdery mildew fungal haustorium is inhibited by the overexpression of Arabidopsis ADF6 but not by the overexpression of ADF5 (Wang et al, 2009).…”
mentioning
confidence: 99%
“…34 Direct evidence for a role for F-actin in HR-PCD is limited. Several studies have shown that cytochalasins affect resistance to pathogens, 48 suggesting a role for actin polymerisation, but as resistance is not always accompanied by HR-PCD, we do not consider these studies here. More direct evidence for a role for the actin cytoskeleton in HR-PCD is provided by data showing that cytochalasins can suppress cell death triggered by Phytophthora infestans in potato; cytochalasin D treatment also delayed induction of key defence markers and decreased the accumulation of PR proteins, with concomitant alleviation of cell death in potato tubers treated with P. infestans cell wall extracts (Figure 2b).…”
Section: Evidence That Actin Dynamics Are Involved In Mediating Pcdmentioning
confidence: 99%
“…Only actin-depolymerising factor (ADF) has been shown to have a role in the regulation of HR-PCD. 48,52 ADF severs F-actin, promotes dissociation of monomeric actin from the pointed end and increases F-actin turnover, 54 so is important for the reorganisation of actin filaments. Proteomic analysis of Petunia flowers reveals downregulation of a basic isoform and upregulation of an acidic isoform of ADF, 15 suggesting ADF may be phosphorylated during senescence.…”
Section: How Is Regulation Of the Cytoskeleton To Mediate Pcd Achieved?mentioning
confidence: 99%
“…Evidence largely comes from studies using actin cytoskeleton-disrupting agents, such as cytochalasins. Treatments with a variety of cytochalasins were shown to increase the penetration rate of both adapted and nonadapted pathogens in multiple plant-pathogen systems, thereby implicating the actin cytoskeleton as having a role in basal defenses and nonhost resistance (Kobayashi et al, 1997;Yun et al, 2003;Shimada et al, 2006;Miklis et al, 2007). The actin cytoskeleton may also play a role in race-specific resistance (Skalamera and Heath, 1998).…”
mentioning
confidence: 99%